Photovoltaic characteristics of solar cells based on Ag/SnS thin film fabricated by the radio frequency sputtering method - Trần, Hữu Toàn; Nguyễn, Tiến Đại; Vũ, Thị Kim Liên; Trương, Thị Hiên; Vũ, Thị Bích; Nguyễn, Mạnh Hùng (Hue University Journal of Science: Natural Science, 2021)
We report the characteristics of solar cells manufactured with silver deposited on SnS thin film (Ag/SnS) synthesized with the radio frequency sputtering method. The Ag/SnS film significantly improves the reliable photocurrent density (JSC), photoconversion efficiency, long-term stability due to high transfer carriers of Ag/SnS, suppressed leakage current, and low surface resistance based on sufficient ohmic contact. The Ag/SnS film-based solar cell obtains a power conversion efficiency (h) of 4.83% with a short circuit current density (JSC) of 15.1 mA/cm2 and open-circuit voltage (VOC) of 0.5 V at room temperature. Based on these findings, we propose a potential application of noble metals on the SnS film for enhancing the efficiency and long-term stability of SnS film–based solar cells.